Cytotoxicity test of 40, 50 and 60% citric acid as dentin conditioner by using MTT assay on culture cell line - Christian Khoswanto; Ester Arijani; Pratiwi Soesilawati (Dental Journal (Majalah Kedokteran Gigi), 2008)
Background: Open dentin is always covered by smear layer, therefore before restoration is performed, cavity or tooth which has been prepared should be clean from dirt. The researchers suggested that clean dentin surface would reach effective adhesion between resin and tooth structure, therefore dentin conditioner like citric acid was used to reach the condition. Even though citric acid is not strong acid but it can be very erosive to oral mucous. Several requirements should be fulfilled for dental product such as non toxic, non irritant, biocompatible and should not have negative effect against local, systemic or biological environment. Cytotoxicity test was apart of biomaterial evaluation and needed for standard screening. Purpose: This study was to know the cytotoxicity of 40, 50, 60% citric acid as dentin conditioner using MTT assay. Method: This study is an experimental research using the Post-Test Only Control Group Design. Six samples of each 40, 50 and 60% citric acid for citotoxicity test using MTT assay. The density of optic formazan indicated the number of living cells. All data were statistically analyzed by one way ANOVA. Result: The percentage of living cells in 40, 50 and 60% citric acid were 95.14%, 93.42% and 93.14%. Conclusion: Citric acid is non toxic and safe to be used as dentine conditioner.